2006
DOI: 10.1002/hc.20190
|View full text |Cite
|
Sign up to set email alerts
|

Stannic chloride-induced unsymmetrical CSe bond cleavage of bis(N,N-dimethylcarbamoylseleno)methanes: Novel generation of selenoaldehydes

Abstract: Treatment of bis(N,N-dimethylcarbamoylseleno)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Bis( N,N ‐dimethylcarbamoyl) ditelluride ( 1 ) was at first prepared in moderate yield by treating N,N ‐dimethylformamide (DMF) with sodium and elemental tellurium under heating followed by aerobic oxidation of the reaction mixture . Preparation of bis( N,N ‐diethylcarbamoyl) ditelluride ( 2 , R 1 = C 2 H 5 ) was also carried out by treating N,N ‐diethylformamide (DEF) with lithium metal and elemental tellurium through a similar procedure as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bis( N,N ‐dimethylcarbamoyl) ditelluride ( 1 ) was at first prepared in moderate yield by treating N,N ‐dimethylformamide (DMF) with sodium and elemental tellurium under heating followed by aerobic oxidation of the reaction mixture . Preparation of bis( N,N ‐diethylcarbamoyl) ditelluride ( 2 , R 1 = C 2 H 5 ) was also carried out by treating N,N ‐diethylformamide (DEF) with lithium metal and elemental tellurium through a similar procedure as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…In the course of our studies on the novel generation of higher‐row chalcogenocarbonyl compounds, we previously reported a convenient preparation of stable ditelluroacetal derivatives A through the reaction of in situ generated tellurocarbamate ions with gem‐dihaloalkanes . Actually, such ditelluroacetals A are recognized as potent precursors for telluroaldehydes B in the light of their symmetrical structures with an easily removable electron‐withdrawing carbamoyl group on each tellurium atom, and compouds A are expected to undergo SnCl 4 ‐induced unsymmetrical C–Te bond cleavage to generate telluroaldehydes B through push–pull type removal of N,N ‐diethyltellurocarbamate in an analogous manner of our previous report on the generation of selenoaldehydes from bis( N,N ‐dimethylcarbamoylseleno)methanes . According to our expectation as mentioned above, we started our exploration on the reaction of A with SnCl 4 in the presence or absence of trapping agents.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, bis(R‐carbonyl)diselenides, RC(O)SeSeC(O)R, reported to date correspond to compounds with aromatic (R–) substituents rather than aliphatic analogs, probably because of a higher thermal stability of aromatic species. Among the few reports of the aliphatic derivatives, the molecule [Me 2 NC(O)Se] 2 , for example, was used by Gong et al , as the starting reagent to obtain a series of new compounds of general formula Me 2 NC(O)SeRSeC(O)NMe 2 . Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our successive studies on the synthesis of higher-row chalcogenocarbonyl compounds, we have found a convenient synthesis of dialkenyl diselenides C through the reaction of ptoluenesulfonylhydrazones A, derived from ketones possessing an α-methylene group, with a base and elemental selenium. [18][19][20][21][22][23][24] The reaction was assumed to proceed through the in situ generated alkeneselenolate ions B via Bamford-Stevens type reaction of ptoluenesulfonylhydrazones [25][26][27][28][29][30][31][32][33] as shown in Scheme 1, and, therefore, the synthetic application of this sequence to the preparation of various selenium-containing heterocyclic compounds was keenly expected.…”
mentioning
confidence: 99%